2014
DOI: 10.1371/journal.pone.0100993
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Inhibitor of Human RAD51 Potentiates Breast Cancer Cell Killing by Therapeutic Agents in Mouse Xenografts

Abstract: The homologous recombination pathway is responsible for the repair of DNA double strand breaks. RAD51, a key homologous recombination protein, promotes the search for homology and DNA strand exchange between homologous DNA molecules. RAD51 is overexpressed in a variety of cancer cells. Downregulation of RAD51 by siRNA increases radio- or chemo-sensitivity of cancer cells. We recently developed a specific RAD51 small molecule inhibitor, B02, which inhibits DNA strand exchange activity of RAD51 in vitro. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 45 publications
4
105
0
Order By: Relevance
“…Depending on the availability of the building blocks, the cinnamide analogues (B) were also constructed by Heck coupling of the corresponding aromatic bromide with acrylamide C. After introducing motif 1 as an amine through amide coupling (D to E), the intermediates were cyclized under mild dehydration conditions with iodine and hexamethyldisilazine 18 to give the desired quinazolinone products (F). In this way, one series of compounds incorporated alkyl and cycloalkyl substituents (1)(2)(3)(4)(5)(6)(7)(8), and another series contained substituted aromatics with a variable spacer -(CH 2 )n-(n =0-2, 9-27). The latter series was designed to optimally target residues F195 and Y191 through piinteractions.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the availability of the building blocks, the cinnamide analogues (B) were also constructed by Heck coupling of the corresponding aromatic bromide with acrylamide C. After introducing motif 1 as an amine through amide coupling (D to E), the intermediates were cyclized under mild dehydration conditions with iodine and hexamethyldisilazine 18 to give the desired quinazolinone products (F). In this way, one series of compounds incorporated alkyl and cycloalkyl substituents (1)(2)(3)(4)(5)(6)(7)(8), and another series contained substituted aromatics with a variable spacer -(CH 2 )n-(n =0-2, 9-27). The latter series was designed to optimally target residues F195 and Y191 through piinteractions.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 99%
“…A D-loop assay confirmed B02 specificity for human RAD51 over its bacterial homologue RecA and other human HR proteins 15 . In vitro, B02 inhibited irradiation-induced RAD51 foci formation, HR repair of dsDNA breaks 7 and sensitized cells to a panel of chemotherapy drugs 5,7 . In vivo B02 significantly enhanced the therapeutic effect of cisplatin in a TNBC xenograft model 5 .…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In human cells, B02 has been shown to interfere with the DNA strand exchange and the nuclear foci formation catalyzed by the DNA repair protein RAD51. RAD51 is required to repair DNA double strand breaks during meiosis and in response to DNA damaging agents [53][54][55]. Examination of the pharmacological effect of B02 in C. elegans revealed that this inhibitor caused sterility in the oct-1 null mutant.…”
Section: Oct-2 Transports the Rad51 Inhibitor B02mentioning
confidence: 99%